Kualitas Morfologi Sel Asites Setelah Dilakukan Fiksasi Alkohol 96% dan NBF 10% pada Sediaan Sitologi Pewarnaan Hematoksilin-Eosin (HE)" - Yohanes Ardian; Eviomitta Rizki; Adinugraha Amarullah; Marinta Marinta (INSOLOGI: Jurnal Sains dan Teknologi, 2025)
Ascitic fluid is an important specimen in diagnostic cytology for detecting malignancy and inflammation within the peritoneal cavity. The accuracy of cytological interpretation depends on cellular morphology, which is influenced by the type and effectiveness of fixation. Fixatives help preserve cellular integrity prior to Hematoxylin–Eosin (HE) staining. Alcohol 96% acts as a coagulative fixative that rapidly denatures proteins, whereas 10% Neutral Buffered Formalin (NBF) is a non-coagulative fixative that forms protein cross-links, providing greater structural stability but requiring longer fixation time. This study aimed to evaluate and compare the morphological quality of ascitic fluid cells fixed with 96% alcohol and 10% NBF on HE-stained cytological preparations to determine the most optimal fixative. A quantitative comparative design with a laboratory-based observational approach was used. Six ascitic fluid specimens were fixed with 96% alcohol for 15 minutes and 10% NBF for 24 hours. Thin smear preparations were stained with HE and assessed for nuclear clarity, cytoplasmic integrity, and staining artifacts using an ordinal score of 1–4. Data were analyzed using the Mann–Whitney U test at a 95% confidence level (α = 0.05). Results showed that 96% alcohol produced clearer nuclear details, sharper cytoplasmic borders, and fewer artifacts than 10% NBF. Although NBF provided stable cellular structures, nuclei appeared darker and cytoplasmic homogeneity decreased due to prolonged fixation. Statistical analysis showed a significant difference (p < 0.05). Thus, 96% alcohol offers superior ascitic cell morphology and serves as an efficient alternative fixative for body fluid cytology.